Indonesian Religious Court Decisions on Child Custody Cases: Between Positivism and Progressive Legal Thought - Suci Ramadhan; JM. Muslimin (JURIS (Jurnal Ilmiah Syariah), 2022)
Indonesian judges of Religious Court in deciding child custody cases have different legal reasoning. Some preferred to use juridical reasoning and others use progressive and sociological reasoning. This different legal reasoning causes various insights in the meaning of justice for child custody. This study aims to analyze the positivistic and progressive Islamic legal thought in judges' decisions of child custody cases. This is normative legal research with statutory and case approaches. The legal material is six judges' decisions and is supported by books, scientific article, statutes, and interview. Then, it is analyzed by content analysis. The result states that judges who use textual reasoning tend to decide that child custody is the mothers right, referring textually to an article 105 of the Islamic Law Compilation. Meanwhile, the other judges who prefer to contextual reasoning, decide that child custody is the fathers right. The textual reasoning is steered by legal-positivism: logical coherence of the text is the main method in concluding decision. The contextual reasoning is driven by sociological as well as critical-progressive thought: deconstruction of legal text, contra legem approach by qiyâs (analogy) and istiḥsân (legal teleology), to produce the justice values based on child interests and parents conditions.